Monte Carlo method used to determine scatter fractions for estimating secondary gamma-ray and X-ray photon dose equivalent rates. Issue 2 (23rd May 2014) - Bourgois, L.; Comte, N.
<x content-type="archive" xml:space="preserve">Abstract</x> The Monte Carlo MCNPX code is used to calculate the scatter fraction, making it possible to assess the scattered dose equivalent rate. Two materials are considered for the phantom: water and steel. The calculations are performed by considering beams of monoenergetic photons (in the range 10 keV to 10 MeV) and bremsstrahlung photons resulting from the interaction of electrons (30–900 keV) on a tungsten target. The variation of the scatter fraction is investigated as a function of the primary photon energy, the beam area at the phantom surface, the scattering angle, and filtration of the bremsstrahlung radiation. We note the shortcomings of the ISO standard issued in 2011, which does not take into account the beam area at the phantom surface, the scattering angle or the scattering materials, thus producing inconsistencies with the computed values given in this study and in the literature. Our values for the scatter fraction are comparable with those given in the literature (e.g. NCRP). As regards the bremsstrahlung radiation, we note the influence of filtration, in particular at low energies. The scatter fractions given here are compatible with the calculation of the ambient dose equivalent, whereas in the literature, they are systematically used for the calculation of air kerma rates. We also obtain scatter fractions for water that are higher by a factor of 5 compared with steel.